COMMUNICATION STRATEGY OF BPJS EMPLOYMENT MEDAN BRANCH OFFICE IN DISSEMINATING THE RETIREMENT INSURANCE PROGRAM - Izza, Vanya Nurul; Aslami, Nuri (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
The purpose of this study was to describe the communication strategy of BPJS Employment Medan Branch Office in disseminating the retirement insurance program and to find out the obstacles faced by the Manpower Office in disseminating the retirement insurance program. This study uses a descriptive method with a communication approach. Methods of collecting data through observation, interviews and documents. The results showed that (1) the strategies used by BPJS Employment Medan Branch in the socialization of the retirement insurance program were knowing or identifying the target audience, translating messages in this case the BPJS Employment Law, Government Regulations (PP), Minister of Manpower Regulations (PMTK), BPJS Employment Vision and Mission, Benefits of the retirement insurance program, registration procedures, as well as coordination with the local labor government and social services related to the socialization of the retirement insurance program, (2) Obstacles faced by BPJS Employment Medan Branch Office in socializing the retirement insurance program, especially for determine the audience socialized by participants Currently not workers in charge of processing company data, so the message document is not right on target, as well as to determine the method used when BPJS Employment Medan Branch Office and related agencies. Expected search results This can maximize the form of communication strategies in the socialization of the retirement insurance program in the future and become material for the development of further studies related to the retirement insurance program at BPJS Employment at the Medan Branch Office.